UNJUK KERJA ALAT PEMBUATAN TEPUNG MOCAF TERHADAP REDUKSI HCN DAN PROTEIN SELAMA PENGERINGAN - Yerizam, Muhammad (Politeknik Negeri Sriwijaya, 2018)
The Mocaf flour maker that made for this research consists of grater, dryer and discmill. In this research is caried out design of dryer that the type of belt conveyer dryer by using blower as a source of air suply and combining grater and discmill into one series. The performance test of the tool for this research is reviewed from the analysis of HCN and proteint content for the Mocaf flourproduced from Manihot Glaviozii for drying temperature in the dryer with temperature variations 80, 85, 90, 95 and 100 â„ƒ. Based on the performance test of the tool, the drying process using temperature variations in the dryer affects the results of the reduction of HCN and protein content in the Mocaf flour products produced for drying process with the temperature variation showed that the greater the drying temperature, the greater the reduction of HCN and protein contained in Mocaf flour.The results of HCN analysis contained in Mocaf flour products experienced HCN reduction 66% while in the reduction of protein contained in Mocaf flour 67.83%